Analisis Semiotika Humor Vincent Dan Desta Dalam Youtube Vindes - Wanda Pratama; Eni Murdiati; Anita Trisiah (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
Apart from being a medium for conveying information, YouTube is also used as a means of entertainment, such as the comedy podcast YouTube channel. Podcast comedy programs present humor that can entertain and make the audience laugh. The purpose of this research is to find out the humor shown by Vincent and Desta on Vindes' YouTube. This research is also to find out the style of humor displayed by Vincent and Desta on Vindes' YouTube. The data collection technique uses a purposive sampling analysis technique. While the research method uses qualitative research. The results of this study show that Vincent and Desta's humor on YouTube Vindes uses an affiliation humor style aimed at entertaining with a positive relationship, then Vincent and Desta also display aggressive humor, this humor is negative and self-defeating humor, this humor is self-deprecating.